2021
DOI: 10.1016/j.reuma.2020.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de artrosis sintomática en España: Estudio EPISER2016

Abstract: Introduction: The Spanish Society of Rheumatology carried out the EPISER2000 study in 2020 to determine the prevalence of osteoarthritis and other rheumatic diseases in the Spanish population. Recent sociodemographic changes and lifestyle habits in Spain justified updating the epidemiological data on osteoarthritis and other rheumatic diseases (EPISER2016-study). Objective: To estimate the prevalence of symptomatic osteoarthritis of the cervical spine, lumbar spine, hip, knee and hand in the adult population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…In routine clinical practice in Spain, patients with moderate-to-severe OA chronic pain refractory to standard analgesic treatment with NSAIDs plus opioids reported modest reduction in pain, while presenting a considerable burden of comorbidities, cognitive impairment, and level of dependency in a relatively short period of treatment Consequently, healthcare costs per patient significantly increased for the NHS, particularly when considering treatments with strong opioids; €2472/year vs. €1380/ year with weak opioids INTRODUCTION Osteoarthritis (OA) is a degenerative joint pathology with prevalence varying depending on the affected joint and the criteria used to define the disease [1,2]. Between 6% and 24% of adults have OA with chronic pain of more than 3 months' duration, with incidence increasing with aging [3][4][5]. In Spain, the study on prevalence of rheumatic diseases (EPISER) showed a prevalence of OA in any joint of 29.4% in persons aged over 40 years [5].…”
Section: Key Summary Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…In routine clinical practice in Spain, patients with moderate-to-severe OA chronic pain refractory to standard analgesic treatment with NSAIDs plus opioids reported modest reduction in pain, while presenting a considerable burden of comorbidities, cognitive impairment, and level of dependency in a relatively short period of treatment Consequently, healthcare costs per patient significantly increased for the NHS, particularly when considering treatments with strong opioids; €2472/year vs. €1380/ year with weak opioids INTRODUCTION Osteoarthritis (OA) is a degenerative joint pathology with prevalence varying depending on the affected joint and the criteria used to define the disease [1,2]. Between 6% and 24% of adults have OA with chronic pain of more than 3 months' duration, with incidence increasing with aging [3][4][5]. In Spain, the study on prevalence of rheumatic diseases (EPISER) showed a prevalence of OA in any joint of 29.4% in persons aged over 40 years [5].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…Between 6% and 24% of adults have OA with chronic pain of more than 3 months' duration, with incidence increasing with aging [3][4][5]. In Spain, the study on prevalence of rheumatic diseases (EPISER) showed a prevalence of OA in any joint of 29.4% in persons aged over 40 years [5]. In addition to nociceptive pain, OA is accompanied by increased disability for the activities of daily living, which has a negative effect on health-related quality of life and is one of the main causes of absenteeism (days off from work due to sick leave), resulting in high health and non-healthcare costs for health systems and society [2,5,6].…”
Section: Key Summary Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 6-24% of adults have chronic OA pain and the incidence increases with age [2,3]. In Spain, according to the EPISER study [4], the prevalence of OA in persons aged > 40 years is 29.4%. Therapeutic approaches include non-pharmacological measures, drug treatment and joint replacement surgery in the most disabling cases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mechnikov North-West State Medical University, Saint-Petersburg, e-mail: altkachenko@mail.ru; 2 Samarkand State Medical University, Samarkand In the clinic of traumatology and orthopedics of Mechnikov St. Petersburg State Medical Academy from 01.01.2022 to 15.12.2022, 187 total knee arthroplasty (TKA) in patients with osteoarthritis were performed. Materials from 30 patients aged 40 to 76 years (19 women, 11 men) were taken by random sampling for morphological examination.…”
mentioning
confidence: 99%